Lack of sustained efficacy for alcohol-based surgical hand rubs containing 'residual active ingredients' according to EN 12791. Issue 2 (February 2017) - Kampf, G.; Kramer, A.; Suchomel, M.
Summary: The World Health Organization recommends the use of hand rubs with 'sustained activity' for surgical hand preparation. This review aims to verify whether any of the alcohol-based hand rubs containing non-volatile 'active ingredients' such as chlorhexidine digluconate (CHG), mecetronium ethylsulphate (MES), or ortho-phenylphenol (OPP) provides such sustained efficacy for surgical hand disinfection. Literature was searched to find studies according to EN 12791. Published data sets were analysed to verify whether any of the formulations has a superior efficacy ( P  < 0.01) after 3 h in comparison to the reference procedure. Formulations with 0.5 and 1% CHG in 70% iso-propanol or 61% ethanol were not superior after 3 h. Formulations with 0.2% MES in 45% iso-propanol and 30% n-propanol were also not superior when applied for 1 min (one data set), 1.5 min as currently recommended for use (14 data sets), and 2 min (one data set). When applied for 3 min the formulations were superior in three out of seven data sets. The hand rub with 0.1% OPP in 78.2% ethanol was also not superior to the reference treatment when applied as recommended for 1.5 min. It appears reasonable and responsible to limit the dermal exposure and environmental input to biocidal agents with a clear benefit such as the alcohols. In analogy to avoiding dyes and fragrances in hand rubs, formulations containing 'active' substances without a clear benefit but with potential risks should be avoided when alternative formulations with the same level of antimicrobial activity, dermal tolerance, and user acceptability are available.